Insights into Hydrothermal Treatment of Biomass Blends: Assessing Energy Yield and Ash Content for Biofuel Enhancement - Cubillos-Montecino, F; Diaz-Robles, L; Espinoza-Perez, A; Espinoza-Perez, L (Public Library of Science, 2024)
This study explores the Hydrothermal Carbonization (HTC) treatment of lignocellulosic biomass blends, delving into the influence of several key parameters: temperature, additive nature and dosage, residence time, and biomass composition. Rapeseeds, Pinus radiata sawdust, oat husks, and pressed olive served as the studied biomasses. One hundred twenty-eight experiments were conducted to assess the effects on mass yield (MY), energy yield (EY), higher heating value (HHV), and final ash content (ASH) by a Factorial Experimental Design. The derived model equations demonstrated a robust fit to the experimental data, averaging an R2 exceeding 0.94, affirming their predictive accuracy. The observed energy yield ranged between 65% and 80%, notably with sawdust and olive blends securing EY levels surpassing 70%, while rapeseed blends exhibited the highest HHV at 25 MJ/kg. Temperature emerged as the most influential factor, resulting in an 11% decrease in MY and a substantial 2.20 MJ/kg increase in HHV. Contrastingly, blend composition and additive presence significantly impacted ASH and EY, with all blends exhibiting increased ASH in the presence of additives. Higher initial hemicellulose and aqueous extractive content in raw biomass correlated proportionally with heightened HHV. © 2024 Vallejo et al. This is an open access article distributed under the terms of the Creative Commons Attribution License, which permits unrestricted use, distribution, and reproduction in any medium, provided the original author and source are credited.